2015
DOI: 10.1016/j.jaci.2014.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Increased noneosinophilic nasal polyps in chronic rhinosinusitis in US second-generation Asians suggest genetic regulation of eosinophilia

Abstract: Capsule Summary In this study we found a significantly lower eosinophilia in nasal polyps surgically removed from second-generation Asian patients, similar to studies of native-born patients in Asian countries, suggesting the hypothesis that there may be genetic regulation of eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
90
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 11 publications
(16 reference statements)
2
90
2
Order By: Relevance
“…Most nasal polyps (NPs) in Caucasian patients with CRSwNP are eosinophilic, a state that is frequently associated with asthma. 1 In contrast, recent studies, including ours, have demonstrated that more than half of the patients with CRSwNP in East Asian countries presented with noneosinophilic inflammation. 24 Although genetic and/or environmental factors may contribute to the heterogeneity of CRSwNP, the mechanisms underlying the persistent and exaggerated inflammation in CRSwNP are not fully defined.…”
contrasting
confidence: 61%
“…Most nasal polyps (NPs) in Caucasian patients with CRSwNP are eosinophilic, a state that is frequently associated with asthma. 1 In contrast, recent studies, including ours, have demonstrated that more than half of the patients with CRSwNP in East Asian countries presented with noneosinophilic inflammation. 24 Although genetic and/or environmental factors may contribute to the heterogeneity of CRSwNP, the mechanisms underlying the persistent and exaggerated inflammation in CRSwNP are not fully defined.…”
contrasting
confidence: 61%
“…While many studies have tried to subclassify CRSwNP into eosinophilic and noneosinophilc subtypes, clear criteria for subclassifying eosinophilic and noneosinophilc remain elusive [48]. Most of the literature defines eosinophilic inflammation by examining the number or ratio of eosinophils in polyp tissues [49][50][51][52]. The current cutoffs proposed in the literature to define eosinophilic chronic rhinosinusitis include a tissue eosinophil amount to more than 5% of all leukocytes in five visual fields or a tissue eosinophil count of more than five cells/high power field (HPF).…”
Section: Endotypes Of Chronic Rhinosinusitis: Eosinophilic Versus Nonmentioning
confidence: 99%
“…By comparison, type 2 inflammatory responses characterised by interleukin (IL) 4, IL-5, IL-13 cytokine expression and eosinophilic inflammation are features of CRSwNP 1. This categorisation may, however, be oversimplified as recent studies show that this may be subject to racial and regional differences 2 3. While the majority of Caucasian patients sampled in the USA and Europe have a pronounced infiltration of eosinophils and expression of IL-5 in the NPs, patients with CRSwNP in East Asian countries including Japan, Korea and China, exhibit a mixed inflammatory profile.…”
mentioning
confidence: 99%